Design, fabricate and analysis of semi auto tart printer machines / Muhammad Haziq Md Fauzi and Hazriel Faizal Pahroraji - Md Fauzi, Muhammad Haziq; Pahroraji, Hazriel Faizal (School of Mechanical Engineering, 2023)
Most of Malaysia's small and medium businesses are in the food and beverage industry, as Malaysians are most likely to spend their money on food. There are many different sorts of festivals in Malaysia. Consider the Hari Raya Aidilfitri festival. As we all know, tiny sellers will sell their homemade kueh Raya for a profit during the Eid festival because it has become conventional for Malays to eat it. The Kueh Raya, for example, is tart. As a result, small vendors are usually dealing with a significant volume of orders during the Eid celebration, and the major goal of this project is to assist small vendors who are making homemade tarts by printing a large number of tarts at once. Semi-automatic tart printing machines would assist them by producing many tarts at once. To operate the machines, the user only needs to place the dough and press the button. The machine will automatically print the dough into tart forms